High-speed stretch-shortening cycle exercises as a strategy to provide eccentric overload during resistance training - Hernández-Davó, J. L.; Sabido, R.; Blazevich, A. J. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Resistance exercises eliciting eccentric overload (EO) are considered to strongly promote muscular hypertrophy and broad neuromuscular adaptations but typically require specialized equipment. The aims of these experiments were to assess whether EO is achieved during common high-speed stretch-shortening cycle (SSC) exercises (rebound bench press throw [RBPT] and squat jump [SJ]), and to test the effect of the external load on the EO achieved. Twenty-nine under 18 handball players and fifteen physically active males (24.9 ± 3.2 years) took part in the experiments. Testing consisted of a single set of 6 repetitions with light (25%-30% 1-RM), moderate (50% 1-RM), and heavy (70%-75% 1-RM) loads. Eccentric and concentric force near the zero-velocity point (50-200 ms) as well as eccentric-concentric force ratio (EO; %) were calculated. In RBPT, higher EO values were found at 50% 1-RM than 70% 1-RM in the time interval 50 ms before and after the zero-velocity point. Higher EO values were also found at 50% 1-RM than both 30% 1-RM and 70% 1-RM 100 ms before and after the zero-velocity point. For the SJ, higher EO values were found at 50% 1-RM and 75% 1-RM than 25% 1-RM 100 ms before and after the zero-velocity point. Higher EO values were found at 50% 1-RM than 25% 1-RM 200 ms before and after the zero-velocity point. However, the higher EO values in the SJ were found far from the zero-velocity point. High-speed SSC resistance training provides similar EO to other methods and thus should promote muscle hypertrophy and other neuromuscular adaptations.